An early warning indicator for liquidity shortages in the interbank market. (6th March 2019) - Eross, Andrea; Urquhart, Andrew; Wolfe, Simon
Abstract: This study investigates an early warning indicator for liquidity shortages in the short‐term interbank market. To identify structural breaks and their persistence, an autoregressive two‐state regime switching model is presented. The variability in the LIBOR–OIS spread along with thresholds, which delimit four intensities, reveals regime changes consistent with liquidity crashes. The transition between the states is state dependent, and the posterior estimates for the crisis and noncrisis states are estimated using the Gibbs sampler. We forecast our early warning indicator up to December 2011 and show that the estimates are superior to a random walk with drift. Therefore, the model is an effective early warning indicator of an imminent liquidity shortage impacting the interbank market.